SIOP PODC: Recommendations for supportive care of children with cancer in a low‐income setting1. Issue 6 (25th February 2013) - Israels, Trijn; Renner, Lorna; Hendricks, Marc; Hesseling, Peter; Howard, Scott; Molyneux, Elizabeth
Abstract These supportive care recommendations were prepared to guide doctors who practice in areas with significantly limited resources but who have sufficient infrastructure and training to treat children with cancer with curative intent. The success of any cancer treatment regimen depends largely on the availability and quality of supportive care and this also determines the intensity of treatment that can be delivered. We present practical recommendations on how to prevent infections, general nursing care, management of febrile neutropenia, nutritional assessment and support, treatment of co‐infections and the social support to help prevent failure to complete treatment in resource poor settings. Pediatr Blood Cancer 2013; 60: 899–904. © 2013 Wiley Periodicals, Inc.